Socioeconomic inequalities in suicide mortality in Barcelona during the economic crisis (2006–2016): a time trend study - López-Contreras, Natalia (BMJ Open, 2019)
OBJECTIVES: This study aimed to analyse trends in socioeconomic inequalities in suicide mortality in Barcelona before and after the start of the economic crisis that started at the end of 2008, including both individual factors and contextual factors of the deceased’s neighbourhood of residence. DESIGN: This is a trend study of three time periods: pre-economic crisis (2006–2008), early crisis (2009–2012) and late crisis (2013–2016). SETTING: Total Barcelona residents between 2006 and 2016 (≥25 years of age) and death data derived from the Judicial Mortality Registry of Barcelona. PARTICIPANTS: 996 deaths by suicide between 2006 and 2016 were analysed. PRIMARY AND SECONDARY OUTCOME MEASURES: The outcomes were age-standardised suicide mortality rates and the associations (relative and absolute risk) between suicide mortality and individual and contextual characteristics for the three time periods. RESULTS: From 2006 to 2008, men with a lower educational level were more likely to commit suicide than better educated men (relative risk (RR)=1.46; 95% CI 1.11 to 1.91). This difference disappeared after the onset of the crisis. We found no differences among women. From 2013 to 2016, suicide risk increased among men living in neighbourhoods with higher unemployment levels (RR=1.57; 95% CI 1.09 to 2.25) and among women living in neighbourhoods with a higher proportion of elderly people living alone (RR=2.13; 95% CI 1.15 to 3.93). CONCLUSIONS: We observed risks for suicide among men living in neighbourhoods of Barcelona with higher unemployment levels and among women living in neighbourhoods with a higher proportion of elderly people living alone. Inequalities in suicide mortality according to educational level tended to disappear during the crisis among men. Thus, it is important to continue to monitor suicide determinants especially in times of economic crisis.